2018
DOI: 10.1111/papr.12688
|View full text |Cite
|
Sign up to set email alerts
|

Unique Intradural Inflammatory Mass Containing Precipitated Morphine: Confirmatory Analysis by LESA‐MS and MALDI‐MS

Abstract: Opioids are often used for analgesia via continuous intrathecal delivery by implantable devices. A higher concentration and daily dose of opioid have been postulated as risk factors for intrathecal granuloma formation. We present a 42-year-old female patient with chronic abdominal pain from refractory pancreatitis, with an intrathecal drug delivery device implanted 21 years prior, delivering continuous intrathecal morphine. After many years without concerning physical signs or complaints, with gradual increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…These effects are concentration dependent . The present report of Kim et al . suggests the possibility that other issues secondary to the formation of precipitates may also contribute.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…These effects are concentration dependent . The present report of Kim et al . suggests the possibility that other issues secondary to the formation of precipitates may also contribute.…”
supporting
confidence: 50%
“…I read with interest the excellent report by Kim et al . on a spinal mass resected from a patient 50 mg/mL morphine intrathecally.…”
mentioning
confidence: 95%
“…Even non-opiate drugs such as baclofen may cause the formation of catheter-tip-associated inflammatory masses [12]. Kim et al have reported a case of a patient who had a catheter-tip-associated lesion that was histologically confirmed to be precipitated by morphine after 21 years of intrathecal therapy [13]. The etiopathogenesis of CTG needs further investigation in order to reduce the complication rate of IADP therapy and develop an optimized treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…SCS has become a promising therapy option for FBSS [14]; however, its use in acute pain syndromes caused by conditions that cannot be surgically addressed is rarely discussed in the literature. In this case study of an unresectable CTG, the SCS system provided the patient with long-term pain relief and allowed for the discontinuation of all opioid pain medications [13].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies in the guinea pig, we found that two mu agonists, DMT-DALDA and PZM21, that are not activators of MRGP-r produce little or no mast cell degranulation, do not activate fibroblasts and when infused intrathecally do not produce intrathecal masses (30). Of note, it was recently reported that a spinal mass resected from a patient receiving 50 mg/mL morphine displayed particulates of morphine, in a loculated fluid-filled sac at the catheter tip, suggesting that at concentrations close to solubility in a buffered water environment with restricted diffusion access, particulate formation may occur, and may contribute to the local reaction (31).…”
Section: Role Of Meningeal Mast Cellsmentioning
confidence: 99%